The Experience of Cancer Patient in Traditional Medicine in Hospital - Solikin, Solikin; Budi, Indra; Budi, Indra; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian have a diversity of tribes and cultures that have a great interest in their communities in relation to life, including using traditional medicine as an effort to overcome their health problems. The study aimed to explain how the experience of cancer patients treated in hospitals using traditional medicine. A descriptive qualitative was conducted for this research. Data collected by in-depth interviews. Participants were used as 26 people with cancer who used traditional medicine as a supplement during treatment in Hospital. The results of the study found 8 themes, namely (1) Knowledge of Cancer (2) First time seeking treatment (3) Sources found a diagnosis of Ca (4) Types of Treatment (5) Support obtained from Traditional Medicine (6) beliefs will healing (7) Changes received during traditional medicine (8) Psychological response when first diagnosed with cancer. The experience of participants in the use of traditional medicine as complementary therapy has a good effect for patients. The most difficult experience of participants is to accept the current conditions, so the psychological condition of the participants needs to be considered.